Agricultural production in the Republic of Slovenia - Vrišer, Igor (Geografski zbornik, 2002)
In june 2000, a census of the agricultural sector was carried out in Slovenia. The Statistical Office of the Republic of Slovenia arranged the data on private farms according to "agricultural assessment areas" and for state-owned agricultural companies according to the existing municipalities. Thus organized, the data formed the basis for local and regional analyses of agricultural land use and for calculating the location coefficient (on the basis of comparison with the national average) for agricultural land devoted to the production of wheat, corn, potato, hops, fodder plants, grasslands, and orchards and vineyards. The land proportions of the most important agricultural products, cultures, and categories according to agricultural assessment areas were the basis for determining and specifying the distribution of the main systems of agricultural land use. According to the same methodology, the results acquired can be compared with research from 1960 and 1985. The data on stock farming, that is, on livestock populations and the total stock farming production (expressed in "livestock units"), was processed in a similar manner. Using the structural proportions of livestock, an attempt was made to divide Slovenia into stock farming areas.
Keywords: agrarna geografija; kmetijska proizvodnja; kmetijska zemljišča; raba tal; Slovenia; Slovenija